Development and validation of women's environmental health scales in Korea: severity, susceptibility, response efficacy, self-efficacy, benefit, barrier, personal health behavior, and community health behavior scales - Hee Kyung Kim; Hyun Kyoung Kim (Korean Society of Women Health Nursing, 2021)
Purpose This study aimed to develop the following scales on women's environmental health and to examine their validity and reliability: severity, susceptibility, response efficacy, self-efficacy, benefit, barrier, personal health behavior, and community health behavior scales. Methods The item pool was generated based on related scales, a wide literature review, and in-depth interviews on women's environmental health according to the revised Rogers' protection motivation theory model. Content validity was verified by three nursing professionals. Exploratory factor analysis, convergent validity, and internal consistency reliability were examined. Results The scales included 10 items on severity, 11 on susceptibility, 10 on response efficacy, 14 on self-efficacy, 8 on benefits, 10 on barriers, 17 on personal health behavior, and 16 on community health behavior. Convergent validity with the environmental behavior scale for female adolescents was supported. The Cronbach's α values for internal consistency were good for all scales: severity, .84; susceptibility, .92; response efficacy, .88; self-efficacy, .90; benefits, .91; barriers, .85; personal health behavior, .90; and community health behavior, .91. Conclusion The evaluation of the psychometric properties shows that these scales are valid and reliable measures of women's environmental health awareness and behaviors. These scales may be helpful for assessing women's environmental health behaviors, thereby contributing to efforts to promote environmental health.